Legal Protection for Cinematographic Video Creators Against Copyright Infringement on the TikTok Digital Platform - Allifiya Putri Damayanti; Burham Pranawa; Ananda Megha Wiedhar Saputri (Penerbit Hellow Pustaka, 2025)
The era of globalization, especially in the 21st century, has brought very significant changes in human life, especially in the field of communication. Access to entertainment can now be enjoyed through various social media platforms using mobile phones, one of which is TikTok. This platform has become popular because it is not only an entertainment medium, but also able to generate quite promising profits. This encourages content creators to compete to make videos as interesting as possible in the hope of attracting the attention of other users and increasing the number of views and followers. The formulation of the problem in this study is how legal protection for content creators on TikTok social media if there is a dissemination of videos without permission from the copyright holder, and what is the role and responsibility of TikTok in protecting copyright for videos uploaded on the platform. The research method used by the author is a normative qualitative method with a literature study approach as a data collection technique. The results of this study conclude that legal protection for video creators is regulated in Law Number 28 of 2014 concerning Copyright, specifically in Article 4, Article 9, Article 96 paragraph (1), and Article 113 paragraph (3). In addition, TikTok as a platform also has a role and responsibility by providing settings and privacy features, which are expected to provide protection for users' creative works and prevent copyright infringement that is detrimental to the creators.